The Issue of Military Requisitions in the Parliamentary Debate during the November Uprising of 1830–1831 - Konarski, Marcin (Historia i Polityka, 2022)
The present analysis concerns military requisitions used during the second Polish national uprising in chronological order. The institution of military requisitions was usually caused by shortages in supplying the army with items essential, from its point of view, for carrying out military operations (foodstuffs, means of transport, equipment for soldiers). These shortages were compensated by legal or illegal seizures of private property. The civil and military authorities, if necessary, decided on the compulsory supply of the indicated products and items for the population by means of generally binding regulations. The author bases his discussion on materials from the legislative process and selected archival sources concerning the implementation of the requisitioning provisions of the insurgent parliament.